2013
DOI: 10.1364/ol.38.002861
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive damage resistance threshold in stoichiometric LiNbO_3:Zr crystals

Abstract: Several optical methods including ultraviolet absorption, infrared absorption of the hydroxyl ions, Raman spectroscopy, and the Z-scan method have been used to determine the damage resistance threshold in 0-0.72 mol. % Zr-containing, flux-grown, nearly stoichiometric LiNbO 3 single crystals. All spectroscopical methods used indicate that samples containing at least ≈0.085 mol: % Zr in the crystal are above the threshold while Z-scan data locate the photorefractive damage threshold between 0.085 and 0.314 mol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Periodically poled sLN:Mg (PPLN), in particular, received special attention in quasi-phase-matched frequency conversion devices. 15 Investigations on the critical threshold concentration of ODR ions in HTTSS grown near stoichiometric crystals have been reported for Mg, Zn, In, and Zr ions using alkali fluxed systems, [43][44][45][46] and for Sc using a Li-rich solution; 47 further references and discussion on this topic will be given in Section III C. …”
Section: Growth Of Odr-ion Doped Sln Crystalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Periodically poled sLN:Mg (PPLN), in particular, received special attention in quasi-phase-matched frequency conversion devices. 15 Investigations on the critical threshold concentration of ODR ions in HTTSS grown near stoichiometric crystals have been reported for Mg, Zn, In, and Zr ions using alkali fluxed systems, [43][44][45][46] and for Sc using a Li-rich solution; 47 further references and discussion on this topic will be given in Section III C. …”
Section: Growth Of Odr-ion Doped Sln Crystalsmentioning
confidence: 99%
“…% range have been grown by the HTTSSG technique. 46 All methods (Z-scan, UV, IR, and Raman) used to characterize the sLN:Zr crystals indicated that the photorefractive damage threshold is at about 0.1 mol. % Zr in the crystal.…”
Section: -18mentioning
confidence: 99%
See 2 more Smart Citations
“…The approach proposed for the interpretation of Mg (Zn) doping effects, appeared to be not completely adequate for the trivalent and tetravalent ODRI, thus, a refinement of the current model is required. Certain progress is achieved owing to recent studies in ODRI-doped stoichiometric LiNbO 3 (SLN) crystals, e.g., [10,11].…”
Section: Introductionmentioning
confidence: 99%